Identification of the pillars that direct a university institution towards a smart-campus - Galeano-Barrera, Claudia Jazmín; Bellón-Monsalve, Daniela; Zabala-Vargas, Sergio Andrés; Romero-Riaño, Efrén; Duro-Novoa, Viviana (Universidad Pedagógica y Tecnológica de Colombia, 2018)
This article makes public the main results of the first phase of a research associated with the determination of a general model of an intelligent campus. A review of the literature was made based on a rigorous selection of documents, which has led to the establishment of the pillars that direct the university to carry out smart practices, integrating knowledge management, innovation and sustainability. This model makes the incorporation of institutional elements more flexible, always respecting university autonomy and social inclusion, in order to propose a framework that allows higher education institutions to be guided towards an intelligent development in an integral way that benefits the whole university community.